Measurements of Surgical Volume in Low- and Middle-Income Countries, a Systematic Review - Ifeoluwa Shoyombo; Abraham Genetu; Lye-Yeng Wong; Muhammed Elhadi; Eric Twizeyimana; Grace Paidamoyo Gwini; Rutikanga William; Timothy Hall; Halimah Khalil; Siva Nyanamani Sandrasagran; Monica Langer (Ubiquity Press, 2023)
Background: Surgical volume is a surgical indicator that was described in the Lancet Commission on Global Surgery (LCoGS) and the World Bank World Development Indicators as an important metric for tracking the delivery of surgical care. Objectives: We aimed to characterize the reports on surgical volume (SV) in the existing literature by using a systematic review to assess studies that examine surgical procedures as a ratio of a population (procedures/100,000 population). Methods: The PRISMA guideline was employed in the systematic review of articles that addressed the measurement of SV in low- and middle-income countries (LMICs), with the primary outcome of surgical procedures/100,000 population. Findings: The search result consisted of 6,657 preliminary studies. Following the title and abstract screening, 6,464 articles were excluded, and the remaining 193 were included in the full text review. From the full text review of the 193, only 26 of these articles defined SV as the ratio of number of procedures per population of the catchment/geographical area. The reported SV was a mean of 765, with an SD of 1260 operations per 100,000. The median SV was 180 (min = 0.900, max = 4470). Conclusion: Our findings support the LCoGS assessment of the gap in surgical care. The target for SV is 5000 per 100,000 population, compared to the average of 765 per 100,000 population as found in this review. The challenges for assessing surgical volume gaps are vast, including the nature of written records, which limits SV reports to an absolute number of procedures per year without a reference to the catchment population. For the purpose of tracking SV, we recommend using proxies that account for the capacity of facilities to deliver care regardless of the catchment population.